Reframing Future Risks of Extreme Heat in the United States. Issue 9 (26th September 2018) - Wobus, C.; Zarakas, C.; Malek, P.; Sanderson, B.; Crimmins, A.; Kolian, M.; Sarofim, M.; Weaver, C. P.
Abstract: The goal of this study is to reframe the analysis and discussion of extreme heat projections to improve communication of future extreme heat risks in the United States. We combine existing data from 31 of the Coupled Model Intercomparison Project Phase 5 models to examine future exposure to extreme heat for global average temperatures of 1.5, 2, 3, and 4 °C above a preindustrial baseline. We find that throughout the United States, historically rare extreme heat events become increasingly common in the future as global temperatures rise and that the depiction of exposure depends in large part on whether extreme heat is defined by absolute or relative metrics. For example, for a 4 °C global temperature rise, parts of the country may never see summertime temperatures in excess of 100 °F, but virtually all of the country is projected to experience more than 4 weeks per summer with temperatures exceeding their historical summertime maximum. All of the extreme temperature metrics we explored become more severe with increasing global average temperatures. However, a moderate climate scenario delays the impacts projected for a 3 °C world by almost a generation relative to the higher scenario and prevents the most extreme impacts projected for a 4 °C world. Plain Language Summary: Extreme heat events or heat waves are public health threats and can also cause damages or disruptions to infrastructure, transportation, agriculture, and water or energy resources. Extreme heat events are already more frequent and more intense than they were a generation ago, and they are expected to become even more frequent and more intense as global average temperatures continue to increase. The way most climate scientists describe future changes in the risk of extreme temperatures can be confusing to nontechnical audiences, who may find it challenging to relate to the projections. In addition, the metric most relevant to what any one person, location, or sector cares about can vary. For example, an urban planner may be concerned about surpassing the temperature threshold at which asphalt softens or rails warp, while a water manager may want to track the number of consecutive days in a heat wave to prepare for changes in water supply, and a public health official may care about high minimum (usually elevated nighttime) temperatures to plan appropriate health adaptation responses. To help characterize risk of extreme heat events to multiple audiences, this analysis uses notable heat waves from the recent past as a benchmark and shows how the frequency and severity of events like these are projected to change in the future for specific levels of global warming (1.5, 2, 3, or 4 °C) above preindustrial levels. With this method, an individual or community can use their own experience as context for understanding how future changes in the frequency, intensity, or duration of such events may differ from current conditions where they live, or from their recollection of a recent heat wave. For instance, someone who remembers the Atlanta heat wave on 10 August 2007 will learn that peak temperatures similar to that event will occur on average 19 times each year, or approximately once every 8 days each summer, if global temperatures rise 4 °C. Having a better and more intuitive understanding of the risks of extreme heat events can inform mitigation, adaptation, or other decision‐making activities. Key Points: We used CMIP5 data to characterize extreme heat risk in the United States for global average temperature changes ranging from 1.5 to 4 degrees Celsius As global temperatures warm, historically rare extreme heat events in the United States are projected to become increasingly common A moderate climate scenario delays impacts by almost a generation relative to the higher scenario and prevents the most extreme impacts